Immunomodulatory effect of a decellularized skeletal muscle scaffold in a discordant xenotransplantation model - Fishman, Jonathan M. (National Academy of Sciences, 2013)
Decellularized (acellular) scaffolds, composed of natural extracellular matrix, form the basis of an emerging generation of tissue-engineered organ and tissue replacements capable of transforming healthcare. Prime requirements for allogeneic, or xenogeneic, decellularized scaffolds are biocompatibility and absence of rejection. The humoral immune response to decellularized scaffolds has been well documented, but there is a lack of data on the cell-mediated immune response toward them in vitro and in vivo. Skeletal muscle scaffolds were decellularized, characterized in vitro, and xenotransplanted. The cellular immune response toward scaffolds was evaluated by immunohistochemistry and quantified stereologically. T-cell proliferation and cytokines, as assessed by flow cytometry using carboxy-fluorescein diacetate succinimidyl ester dye and cytometric bead array, formed an in vitro surrogate marker and correlate of the in vivo host immune response toward the scaffold. Decellularized scaffolds were free of major histocompatibility complex class I and II antigens and were found to exert anti-inflammatory and immunosuppressive effects, as evidenced by delayed biodegradation time in vivo; reduced sensitized T-cell proliferative activity in vitro; reduced IL-2, IFN-γ, and raised IL-10 levels in cell-culture supernatants; polarization of the macrophage response in vivo toward an M2 phenotype; and improved survival of donor-derived xenogeneic cells at 2 and 4 wk in vivo. Decellularized scaffolds polarize host responses away from a classical TH1-proinflammatory profile and appear to down-regulate T-cell xeno responses and TH1 effector function by inducing a state of peripheral T-cell hyporesponsiveness. These results have substantial implications for the future clinical application of tissue-engineered therapies.